Supporting the academic success of first-year students in South Africa: A study of the epistemological access they acquired through a lecture and text - Rusznyak, L.; Dison, L.; Moosa, M.; Poo, M. (South African Journal of Higher Education, 2017)
Much is at stake with regard to academic success of first-year students in higher education. This paper presents the findings of an empirical study which looks at shifts in students’ understanding of a concept through a systematic sequence of learning opportunities in a university-based course. While 89% of participants could satisfactorily identify criteria of the concept following an introductory lecture, only 41% could adequately articulate their understanding of that concept. One third of the participants did not read the prescribed text. For students who did the reading, lectures and the provision of reading materials provided sufficient opportunities for half of them satisfactorily to comprehend the requisite concepts. Consolidation in a follow-up session is necessary to provide additional opportunities for students adequately to comprehend a concept.